If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -5(x + 3) = 7 + -1(5 + x) Reorder the terms: -5(3 + x) = 7 + -1(5 + x) (3 * -5 + x * -5) = 7 + -1(5 + x) (-15 + -5x) = 7 + -1(5 + x) -15 + -5x = 7 + (5 * -1 + x * -1) -15 + -5x = 7 + (-5 + -1x) Combine like terms: 7 + -5 = 2 -15 + -5x = 2 + -1x Solving -15 + -5x = 2 + -1x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add 'x' to each side of the equation. -15 + -5x + x = 2 + -1x + x Combine like terms: -5x + x = -4x -15 + -4x = 2 + -1x + x Combine like terms: -1x + x = 0 -15 + -4x = 2 + 0 -15 + -4x = 2 Add '15' to each side of the equation. -15 + 15 + -4x = 2 + 15 Combine like terms: -15 + 15 = 0 0 + -4x = 2 + 15 -4x = 2 + 15 Combine like terms: 2 + 15 = 17 -4x = 17 Divide each side by '-4'. x = -4.25 Simplifying x = -4.25
| 12x-4=8x-37 | | 8/5x-3=16-2/5x | | P^2-14p+24=0 | | 3(v-2)-6v= | | 4(4-7n)=2(8-n) | | -6x+-5x= | | (46+2x)(65+2x)=4740 | | 3r^2-24r+45=0 | | 12p^2+8p+1=0 | | 3y^3+16y+5=0 | | 4(-b+7)=-(1+7v) | | (x-8)(x+7)=56 | | 17x+-12=114+3 | | 5g^2+44g-9=0 | | 5x+2(5x+8)=8x+18 | | 6p+-3(4p+3)+4(6p+1)=43 | | 5(m-2)=-(6m-1) | | x(x-9)(x+3)=0 | | Z-6.8=7.56 | | 0=6x+x^2-31 | | 1620x-350=680x+470 | | 1/3p-p=12 | | (8x+3)(5x+8)=180 | | 3x+9(3x+1)=9x-6 | | 6(4x+3)=138 | | 5x+9i=10-3yi | | 2x+9+9x-8=8x+19 | | 15x-3(6+5x)=-18 | | x*x=16+(x+-4)(x+2) | | 8+6y=7y | | 2x+6=-6-2 | | -4(v+7)=-(1+7v) |